Neurotisisme dan Perilaku Phubbing Pada Mahasiswa - Rahmatullah, Muh Asri; Asri, Asmulyani; Fakhri, Nurfitriany (Jurnal Psikologi TALENTA, 2024)
The aim of this study is to know the effect of neuroticism to phubbing behavior on college student. This study used quantitative method as an approach. The respondent that involved in this study are 150 college students (n=150, 40 men and 110 women), using accidental sampling as a sampling technique. This study used two instruments, they are neuroticism scale and phubbing scale that arrange as Likert scale. The neuroticism scale developed by researcher based on neuroticism aspect by McCrae dan Costa (α=0,932, and validity score range 0,369 – 0,782). The phubbing scale that is used in this study is an adaptation scale from Zulfikar, this scale developed based on two aspects from Karadağ, (α=0,892, and validity score range 0,380 – 0,702). The data of this study was analyzed use Ordinal Regression test with significance value 0,000 (p<0,05) and Nagelkerke value is 0,261 (H1 accepted). It means Neuroticism can affect phubbing behavior on college students at Makassar State University and the contribution of the effect is 26,1%. People with high neuroticism will cause excessive use of cell phones to reduce negative feelings, this excessive use of cell phones implicated to phubbing behavior appear and increase.